PENDEKATAN MUHAMMADIYAH DALAM MENANGANI PORNOAKSI DAN PORNOGRAFI DI ERA INDUSTRI 5.0 STUDI KASUS DAN ANALISIS STRATEGIS - Rina Hasibuan, Wilda; Ekawati, Nia; Fathurohman, Oman (Jurnal Informatika Kaputama (JIK), 2025)
The phenomenon of pornoaction and pornography is increasingly concerning in the Industry 5.0 era, characterized by rapid advancements in digital technology and unlimited access to information. Muhammadiyah, one of the largest Islamic organizations in Indonesia, employs a strategic approach to tackle this issue by integrating Islamic values, fatwas from the Indonesian Ulema Council (MUI), and national regulations. This paper examines Muhammadiyah’s implementation of character education and digital literacy programs, alongside a strategic analysis of pornography prevention through case studies and synergy with legal policies. The findings indicate that Muhammadiyah’s approach effectively builds moral resilience in society and adapts well to the digital challenges of Industry 5.0.